Linking Gait Dynamics to Mechanical Cost of Legged Locomotion - Lee, David V.; Harris, Sarah L. (Frontiers in Robotics and AI, 2018)
For millenia, legged locomotion has been of central importance to humans for hunting, agriculture, transportation, sport, and warfare. Today, the same principal considerations of locomotor performance and economy apply to legged systems designed to serve, assist, or be worn by humans in urban and natural environments. Energy comes at a premium not only for animals, wherein suitably fast and economical gaits are selected through organic evolution, but also for legged robots that must carry sufficient energy in their batteries. Although a robot’s energy is spent at many levels from control systems to actuators, we suggest that the mechanical cost of transport is an integral energy expenditure for any legged system — and measuring this cost permits the most direct comparison between gaits of legged animals and robots. Although legged robots have matched or even improved upon total cost of transport of animals, this is typically achieved by choosing extremely slow speeds or by using regenerative mechanisms. Legged robots have not yet approached the low mechanical cost of transport achieved at speeds used by bipedal and quadrupedal animals. Here we consider approaches used to analyze gaits and discuss a framework, termed mechanical cost analysis (MCA), that can be used to evaluate the economy of legged systems. This method uses a point-mass perspective to evaluate the entire stride as well as individual events that accrue mechanical cost. The analysis of gait began at the turn of the last century with spatiotemporal analysis facilitated by the advent of cine film. This gave rise to the “gait diagram” that plots duty factors and phase separations between footfalls. This approach was supplanted by methods using force platforms to determine forces and motions of the center of mass (CoM) — and models that characterize gait according to fluctuations in potential and kinetic energy. MCA draws from both of these approaches and provides a unified framework that interprets the spatiotemporal sequencing of leg contacts within the context of CoM dynamics to determine mechanical cost of transport in each instance of the stride. Future studies of gait in biological and engineered systems can be compared using MCA.